Enhancing Students' Critical and Creative Thinking Skills Through Problem-Based Learning - Mulyati, Yayuk; ‘Ainunnizar, Desy; Hasan, Said; Wicaksono, Azizul; Ichsan, Mochammad (Indonesian Journal of Biology Education, 2024)
The critical and creative thinking skills (CCTs) of junior high school students remain at a low level. Following this phenomenon, this research was conducted to explore the potential of the Problem Based-Learning model (PBL) to enhance students' CCTs, using a single class with a single group pretest-posttest design involving the ninth-grade students from State Junior High School in Malang, Indonesia. The sample was selected using the purposive sampling technique. Data was gathered through evaluation instruments in the form of pretest and posttest results. In addition to the aforementioned instruments, teaching modules and student worksheets were employed in the data collection process. The data analysis was performed using a number of tests, including the Shapiro-Wilk data normality test, Wilcoxon test, and N-Gain test. In particular, these tests were carried out to evaluate changes in scores. The research findings indicated that the implementation of PBL was effective and significantly successful in improving students' thinking skills, especially their CCTs. This is evidenced by the Wilcoxon test results, which resulted a significance value of less than 0.05, as well as a high N-Gain increase for critical thinking (0.7001) and a medium category for creative thinking (0.5826). Therefore, these findings can serve as recommendations concerning the role of PBL in improving students' two thinking skills (CCTs).